2018
DOI: 10.1113/jp274955
|View full text |Cite
|
Sign up to set email alerts
|

When muscle Ca2+ channels carry monovalent cations through gating pores: insights into the pathophysiology of type 1 hypokalaemic periodic paralysis

Abstract: Patients suffering from type 1 hypokalaemic periodic paralysis (HypoPP1) experience attacks of muscle paralysis associated with hypokalaemia. The disease arises from missense mutations in the gene encoding the α1 subunit of the dihydropyridine receptor (DHPR), a protein complex anchored in the tubular membrane of skeletal muscle fibres which controls the release of Ca from sarcoplasmic reticulum and also functions as a Ca channel. The vast majority of mutations consist of the replacement of one of the outer ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Very few data on Cav1.1 structure-function relationship are available in fully differentiated skeletal muscle fibers, except in the context of muscle diseases for which genetically engineered mouse models have been generated or mutated Cav1.1 have been transfected [26]. Also, it is always questionable if data obtained in cultured muscle cells or in heterologous expression systems, which, moreover, is only recently possible, are transferable to fully differentiated skeletal muscle fibers [27].…”
Section: Discussionmentioning
confidence: 99%
“…Very few data on Cav1.1 structure-function relationship are available in fully differentiated skeletal muscle fibers, except in the context of muscle diseases for which genetically engineered mouse models have been generated or mutated Cav1.1 have been transfected [26]. Also, it is always questionable if data obtained in cultured muscle cells or in heterologous expression systems, which, moreover, is only recently possible, are transferable to fully differentiated skeletal muscle fibers [27].…”
Section: Discussionmentioning
confidence: 99%
“…The absolute changes of activity of these ions are poorly characterized at rest, in activity, and possibly during cell stretching and therefore deserve to be scrutinized. The use of this method should be also essential for exploring perturbations of ion activity that have been suggested to exist in a number of muscle channelopathies including periodic paralysis (Cannon, 2015;Allard and Fuster, 2018). Finally, one may hope that this study will contribute to the dissemination of muscle electrophysiology, which unfortunately has become scarce, and help muscle physiologists realize how critical it is to control voltage when investigating the movements of ions including the ubiquitous Ca 2+ ion.…”
mentioning
confidence: 98%
“…Apart from two mutations—one localized in the S3 segment of domain III (V876E) and one in the S4-S5 loop of domain III (H916Q)—all HypoPP1 mutations consist of a substitution of the first or second outermost basic residue with a less charged amino acid (histidine, serine, or glycine) in the voltage-sensing S4 segment of domain II (R528H/G), domain III (R897S, R900S), or domain IV (R1239H/G) (Cannon, 2010; Matthews and Hanna, 2010; Jurkat-Rott et al, 2012; Moreau et al, 2014; Allard and Fuster, 2018). Long before the identification of HypoPP1 mutations (Jurkat-Rott et al, 1994; Ptácek et al, 1994), early experiments performed in muscle fibers from HypoPP1 patients’ muscle biopsies had shown that diseased muscle cells were abnormally depolarized in low K + external solution to the point of rendering cells inexcitable (Rüdel et al, 1984; Ruff, 1999).…”
mentioning
confidence: 99%
“…Along this line, the STAC3-coexpressed Cav1.1 L-type Ca 2+ current in oocytes was not found to inactivate in response to maintained depolarization, whereas a well identified voltage-dependent inactivation mechanism is known to occur in fully differentiated muscle fibers (Collet et al, 2003; Ursu et al, 2004). The presence of a native muscle environment for the transfected channel is the main advantage of the in vivo mouse model system (Fuster et al, 2017a,b; Allard and Fuster, 2018). Inversely, in this system, the endogenous mouse Ca 2+ channels are not entirely replaced by the transfected channels so that the biophysical properties of the Ca 2+ channel inevitably correspond to a mixture of the biophysical properties of endogenous and transfected channels.…”
mentioning
confidence: 99%